Structural and functional brain imaging in adult attention-deficit/hyperactivity disorder. (April 2010) - Cubillo, Ana; Rubia, Katya
Attention-deficit/hyperactivity disorder (ADHD) is a childhood disorder that persists into adulthood. Nevertheless, there are far fewer imaging studies in adult compared with childhood ADHD. Here we review the imaging literature on brain structure, function and structural and functional connectivity in adult ADHD, as well as the effects of psychostimulants on brain dysfunctions. Importantly, we discuss similarities and differences between these deficit findings and those in childhood ADHD to address the key question of continuity of brain abnormalities into adulthood. Findings show strikingly similar but more inconsistent abnormalities in adult ADHD in key childhood ADHD deficit areas of frontostriatal, temporoparietal and cerebellar regions, presumably due to highly prevalent confounding factors in adult ADHD of elevated rates of comorbidity and medication history.